“How Long Have I Got?” in Stage IV NSCLC Patients With at Least 3 Months Up to 10 Years Survival, Accuracy of Long-, Intermediate-, and Short-Term Survival Prediction Is Not Good Enough to Answer This Question - Guo, Huiru; Li, Hegen; Zhu, Lihua; Feng, Jiali; Huang, Xiange; Baak, Jan P. A. (Frontiers in Oncology, 2021)
Background: Most lung cancer patients worldwide (stage IV non-small cell lung cancer, NSCLC) have a poor survival: 25%-30% die <3 months. Yet, of those surviving > 3 months, 10% - 15% (70,000 - 105,000 new patients worldwide per year) survive (very) long. Surprisingly little scientific attention has been paid to the question, which factors cause the good prognosis in these NSCLC stage IV long survivors. Therefore, “How long do I still have?” currently cannot be accurately answered. We evaluated in a large group of 737 stage IV NSCLC patients surviving 3.2-120.0 months, the accuracies of short- and long-term survival predictive values of baseline factors, radiotherapy (RT), platinum-based chemotherapy (PBT) and tyrosine kinase inhibitors targeted therapy (TKI-TT). Methods: Non-interventional study of 998 consecutive first-onset stage IV NSCLC patients. 737 (74%) survived 3.2-120.0 months, 47 refused both RT, PBT and TKI-TT. Single and multivariate survival analysis and Receiver Operating Curve (ROC) analysis were used with Dead-Of-Disease (DOD) or Alive-With-Disease (AWD) as endpoints. Results: The median survival (16.1 months) of 47 patients who refused both PBT, RT and TKI-TT, was significantly worse than those with RT, PBT and/or TKI-TT (23.3 months, HR = 1.60, 95%CI = 1.06-2.42, P = 0.04). Of these latter 690 patients, 42 % were females, 58% males, median age 63 (range 27-85) years, 1-, 2, 5- and 10- year survival rates were 74%, 49%, 16% and 5%. 16% were Alive-With--Disease (AWD) at the last follow-up. subtype (Adenocarcinoma vs. all others), performance score, TNM-substage, the number of PBT-cycles and TKI-TT had independent predictive value. However, with the multivariate combination of these features, identification results of short-term non-survivors and long-term survivors were poor. Conclusions: In stage IV NSCLC patients with > 3 months survival, baseline features and systemic therapeutic modalities have strong survival predictive value but do not accurately identify short- and long-term survivors. The predictive value of other features and interventions discussed should be investigated in the worldwide very large group of stage IV NSCLC patients with > 3 months survival.